Study of two non-pharmacological methods, progressive muscle relaxation and music, on pain relief of cancerous patients - Shaban M; Rasoolzadeh N; Mehran A; Moradalizadeh F (Tehran University of Medical Sciences, 2006)
Background & Aim: Pain is one of the important complication of chronic diseases such as cancer. Purpose of this study is to investigation of two non-pharmacological methods, progressive muscle relaxation and music, on pain relief in patients suffer from cancer. Methods & Materials: This research is a intervention clinical trial which was done in a hospital affiliated to Tehran University of Medical Sciences. In this study, 100 cancerous patients that have inclusion criteria were selected by simple sampling method. The participants into two groups allocated, 50 patients in progressive muscle relaxation, and 50 patients in music group. Data collection tools were questionnaire, pain level recorded sheet, taps with headphone (is produced by Sony company) and music box including light music consist of classical, mild and Iranian traditional music. Questionnaire was designed in two parts, demographically characteristics and disease characteristics. Data were collected by interview and patient self report. After adequate education to two groups, asked them to perform that method 30minet per day until 3 days. Then, pain level, at previous 24 hours until 3 days were assessed and recorded in related sheet. Analysis of data were analyzed by SPSS software, inferential and descriptive statistics such as Mann Whitney, chi Square, Fisher's exact test, and Friedman. Results: The finding of research showed in both relaxation and music groups there were significant differences in pain level before and after intervention (p<.001). Also there were significant differences between two groups in pain level (p=0.016). It means that pain relief in relaxation group was more significant. Conclusion: According to the findings of this research, although both progressive muscle relaxation and music are effective and decreasing of pain level but progressive muscle relaxation is more effective than music.